KEHIDUPAN SUKU ANAK DALAM BUKIT SUBAN KABUPATEN SAROLANGUN DALAM FOTOGRAFI DOKUMENTER - Wulandari, Teti (Matalensa: Journal of Photography and Media, 2021)
In the creation of this  work, the theme is about the inner tribe of children with the aim of creating documentary photography about the life of the inner tribe and introducing their culture to the outside community. In this  work  I use the theory of journalism photography, photography documentaries, photo stories and cultural theory, using the design preparation method. The realization and presentation of the work.The results obtained in the creation of this work are to know the other side of the tribe of children in their daily  life such as in livelihoods, arts, social, food, crafts and advice before doing a photo shoot really requires careful preparation, both from the concept, time and tools needed as well as in-depth research reset.